2013
DOI: 10.1209/0295-5075/104/28002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of shear thickening oscillation

Abstract: -We report experimental observation of the shear thickening oscillation, i.e. the spontaneous macroscopic oscillation in the shear flow of severe shear thickening fluid. Using density-matched starch-water mixture, in the cylindrical shear flow of a few centimeters flow width, we observed that well-marked vibrations of the frequency around 20 Hz appear via a Hopf bifurcation upon increasing externally applied shear stress. The parameter range and the frequency of the vibration are consistent with those expected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
6
23
0
1
Order By: Relevance
“…As for the boundaries in the rotating axis direction, however, we employ the periodic boundary condition for simplicity. We set diameter of the center rod d = 2, the flow width h = 1.5 and the fluid depth ℓ = 2.6 by the units (11). With the parameters for the present medium, they are comparable with the ones for our experimental set up.…”
Section: Numerical Simulation a Modelmentioning
confidence: 72%
“…As for the boundaries in the rotating axis direction, however, we employ the periodic boundary condition for simplicity. We set diameter of the center rod d = 2, the flow width h = 1.5 and the fluid depth ℓ = 2.6 by the units (11). With the parameters for the present medium, they are comparable with the ones for our experimental set up.…”
Section: Numerical Simulation a Modelmentioning
confidence: 72%
“…In addition, the normal stress difference becomes large when the shear thickening takes place [4,5]. The mechanism of the DST can also be understood by the introduction of an order parameter which exhibits a S-shape in a plane of stress-strain rate (flow curve) [16][17][18][19][20].Although most of previous studies on shear thickening are oriented to dense suspensions, it would be convenient to consider relatively low density systems where kinetic theory tools [21][22][23][24][25] can provide a deeper understanding on the microscopic mechanisms involved in the DST. Indeed, some papers have reported that a DST-like process for the kinetic temperature can take place as a result of a saddle-node bifurcation [26][27][28][29].…”
mentioning
confidence: 99%
“…In addition, the normal stress difference becomes large when the shear thickening takes place [4,5]. The mechanism of the DST can also be understood by the introduction of an order parameter which exhibits a S-shape in a plane of stress-strain rate (flow curve) [16][17][18][19][20].…”
mentioning
confidence: 99%
“…Three-dimensional simulations of dense suspensions were recently performed based on a fluid dynamics model for dilatant fluids where the inertia of the fluid plays a central role [27,46]. This approach accounts for the large and fast "shear-thickening oscillation" observed in the wide-gap Taylor-Couette flow of potato-starch suspensions [47] and predicts localized shear-thickened bands that bear negative pressures but that do not seem to organize or propagate along the vorticity direction [27]. The case of a small-gap Taylor-Couette flow with much smaller inertia and more homogeneous shear rate and volume fraction conditions still remains to be explored numerically as well as experimentally through local wall or particle pressure measurements [48][49][50].…”
Section: Discussion and Interpretation In Terms Of Unstable Vortimentioning
confidence: 99%